AFFECTION IN DIGITAL COMMUNICATION: A COMPARATIVE STUDY OF ENGLISH AND UZBEK SOCIAL MEDIA DISCOURSE (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
This article examines the expression of affection in digital communication through a comparative analysis of English and Uzbek social media discourse. The study focuses on how affectionate meanings are constructed and conveyed in online interaction, taking into account linguistic, cultural, and gender-related factors. In recent years, digital communication platforms such as Telegram, Instagram, and online messaging applications have significantly transformed interpersonal communication, influencing both the forms and strategies of emotional expression.The research is grounded in the theoretical frameworks of Sociolinguistics and Computer-mediated communication. A qualitative comparative method is employed to analyze examples of online communication in English and Uzbek, including messages, comments, and social media interactions. Particular attention is paid to discourse strategies such as direct and indirect affectionate expressions, emoji usage, abbreviations, code-switching, and emotional intensification.